Influence of Cultural Socio-Economic Factors on K.C.S.E Examination Performance in Public Secondary Schools: A Case If Lamu West Sub County, Lamu County, Kenya - Kisaka, Joseph N. (Advances in Social Sciences Research Journal, 2023)
The measure of success in many countries is measured by the Academic performance in national examinations like Kenya Certificate Secondary Education (K.C.S.E.) which is a national examination in Kenya. This study endeavoured to establish the influence of selected cultural factors on the academic performance of students in Lamu West Sub-County in Lamu County in Kenya. The study was carried out in Lamu West Sub-County which has persistently registered low academic performance in national examinations. The cultural factors leading to this poor performance in Lamu Sub-County had not been adequately addressed. The study was guided by the following objectives; to establish the types of cultural factors that influence academic performance in Lamu West Sub-County and the influence of cultural factors on K.C.S.E. academic performance in Lamu West Sub-County. The study adopted a descriptive survey design. The target population comprised of teachers, and Board of Management (B.O.M.) parents. The sample size was 144 teachers and 48 B.O.M parents. The collection of data was by use of questionnaires and interviews. Descriptive statistics were used to analyse the quantitative data while qualitative was analysed through content analysis. The findings were presented by use of frequency distribution tables and percentages. The results showed that cultural factors influenced the Kenya Certificate of Secondary Education (KCSE) national examination in Lamu Sub-County. Interviews from B.O.M parents also provided data to show how these cultural factors influenced KCSE academic performance. Based on the findings, the study established that early pregnancies, gender stereotypes, early marriages as well as the frequent religious cultural practices influenced KCSE academic performance in Lamu West Sub-County. Among the recommendations was that parents should take an active role in advising their children about the importance of education, and also the government should take stern measures against out-dated cultures like early marriages which should be banned.